Development of the regulation of hydrobiological monitoring in circulation cooling system of the Zaporizhzhia nuclear power plant - Yesipova, Natalia; Marenkov, Oleh; Sharamok, Tatiana; Nesterenko, Oleh; Kurchenko, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2022)
The article proposes a new approach to solving the problem of biofouling at the facilities of the circulating cooling system of the Zaporizhzhia Nuclear Power Plant (ZNPP) by regulating hydrobiological studies. In the course of the studies, 4 species of hydrobionts were found that formed massive fouling on water supply facilities: filamentous algae Oedogonium sp. and Ulotrix zonata with a total biomass of 123.6±18.44 g/m2, tropical molluscs Melanoides tuberculata and Tarebia granifera of the Thiaridae family with a biomass of 20.09 g/m2. The shells of dead mollusks drifted along the pipes of the circulation system with the flow of water and interfered with the operation of pumping stations. Also, the blue-green algae Microcystis aeruginosa, which dominated the phytoplankton of the cooling pond, belonged to the potential bio-hindrances. The hydrobiological regulation was developed with the aim of timely detection of hydrobionts capable of active reproduction and creation of biological obstacles. It provides for four types of monitoring: current (operational), extreme (control), deployed (research) and background (hydrobiological monitoring of the Kakhovka reservoir in the zone of influence of waste warm waters). For each type of monitoring, the subjects of control (a group of hydrobionts), control parameters (species composition, abundance, biomass) and frequency of control are determined. The regulation of hydrobiological monitoring makes it possible to minimize the consequences or prevent the occurrence of accidents and emergencies in the operation of the ZNPP cooling circulation systems associated with biological obstacles, and can be used as an example for solving similar problems at other power facilities. The article also contains practical recommendations for improving the ecological state of the cooling pond and preventing the massive development of dangerous aquatic organisms by introducing biomeliorator fish with a different food spectrum into the reservoir